Teologia postu w "Hymnach o poście" św. Efrema Syryjczyka - Uciecha, Andrzej (Vox Patrum, 2020)
The literary output of St. Ephrem consists of biblical commentaries, polemical refutations and meditations in prose, poetic dialogues, metric homilies and hymns (madrāšê). The latter genre calls for major attention since it seems that it was the favourite instrument in Ephrem’s hermeneutical toolbox. Madrāšê were not addressed to monks or eremites. In the fourth century, Eastern Syrian Christianity was focused on deep asceticism practiced in daily life through fasting, vigils and continuous prayer. Such perspective was characteristic of the baptised in general, regardless of whether they were clerics, monks or laypeople. Besides the biblical examples, the main source of imaginary featured in De ieiunio is nature, created by God’s will. In some parts of this madrāšâ, Ephrem creates a balance of two elements, supplementing the biblical text with images taken directly from nature. The keystone of the rich theological message presented across the stanzas of the ten liturgical hymns is Christ – the Word opening the treasure of the Scriptures, the firstborn Son of the Father, the only Righteous, the ultimate model for all fasting ascetics. What matters in fasting is the free will, discipline against hunger and desires, and charity. Ephrem underscores the role of motivation and points out the purifying effects of fasting.